Heat shock factor binding protein BrHSBP1 regulates seed and pod development in Brassica rapa - Muthusamy, Muthusamy; Son, Seungmin; Park, Sang Ryeol; Lee, Soo In (Frontiers in Plant Science, 2023)
Plant heat shock factor binding proteins (HSBPs) are majorly pronounced for their implications in the negative regulation of heat stress response pathways (HSRs). Herein, we study the hitherto unknown functions of the HSBP1 in Brassica rapa (BrHSBP1). BrHBSP1 was predominant in flower buds and young leaves, while its segmental duplicate, BrHSBP1-like, was abundant in green siliques. Abiotic stress conditions such as heat, drought, cold, and H2O2, and phytohormones differentially regulate BrHSBP1. The activity of BrHSBP1-GFP fusion proteins revealed their cellular localization to in nuclei and cytosols. Transgenic overexpression of BrHSBP1 (BrHSBP1 OX ) improved the pod and seed sizes, while CRISPR-Cas BrHSBP1 knockout mutants (Brhsbp1_KO) aborted seed and pod development. The transcriptomic signatures of BrHSBP1 OX and Brhsbp1_KO lines revealed that 360 and 2381 genes, respectively, were differentially (Log2FC≥2, padj<0.05) expressed over the control lines. In particular, developmental processes, including plant reproductive structure developmental (RSD) genes, were relatively downregulated in Brhsbp1_KO. Further, yeast two-hybrid assays confirmed that BrHSBP1 can physically bind to RSD and other genes. Taken together, it is clear that BrHSBP1 is involved in seed development through the modulation of RSD genes. Our findings add a new regulatory player of seed and pod development in B. rapa.